EFEK SAMPING KB SUNTIK DEPOMEDROXY PROGESTERONE ACETATE (DMPA) PADA AKSEPTOR KB SUNTIK DMPA DI DESA TIPAR KIDUL KECAMATAN AJIBARANG KABUPATEN BANYUMAS TAHUN 2011 - Ratih Padmasari; Feti Kumala Dewi (Universitas Harapan Bangsa Purwokerto, 2012)
Background: injectables is one of the many devotees contraception acceptor 323 (15%) and caneffectively delay or space pregnancy. The reasons for selecting the place of research in thevillage Tipar Kidul because of the number of acceptors acceptors with 323 (15%). Acceptor hasa practical reason, easily done 3 months, side effects are few, the location close to wherecontraceptive services and affordable costs.Objective: To determine the picture of interest to follow family planning acceptors and sideeffects of injections for 3 months (DMPA) acceptor injections 3 months (DMPA) In the villageTipar Ajibarang Kidul District Banyumas in 2011.Methods: This study is a descriptive cross-sectional quantitative approach. Samples were 49acceptors. The sampling technique used purposive sampling. The instrument used was aquestionnaire. Data were analyzed by univariate test that uses the results mean.Results: Of the 49 acceptors acceptors largely follow the family planning program aimed tospace pregnancy are 26 acceptors (53.1%). Most of the acceptor states experiencing side effectssuch as menstrual disorders were 38 acceptors (77.6%) and increased weight gain of 22acceptors (44.9%).Conclusion: The aim acceptor program 3 months DMPA injections in Tipar Kidul village tospace pregnancy and most of the acceptor experiencing side effects such as menstrual disorders.Keywords: The aim of family planning programs, the side effects of family planning acceptors3-month injectable (DMPA)